A review of inspiratory muscle training. When and why does it work? - Faghy, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2019)
The need to provide a training stimulus to the respiratory muscles was not considered until the late 1980`s when Professor Jerome Dempsey provided the first insight into how the physiological basis of an elite athlete may predispose their respiratory systems as a limiting factor for performance (Dempsey, 1986). This occurs as the targeted and specific adaptation that occurs within training enables physiological capabilities to be improved, however within training programmes the attention given to the respiratory system is negligible/non-existent. As a result this presents the respiratory system as a potential limitation to whole body exercise performance. The phenomena of respiratory muscle fatigue has been extensively researched by groups across the world in an attempt to understand the consequences of respiratory muscle fatigue in relation to performance. Briefly, there are a number of contributing factors which are important in the development of respiratory muscle fatigue which includes repeated, high force outputs from the diaphragm and accessory respiratory muscles during high intensity exercise tasks. The consequences of respiratory muscle fatigue has negative implications for performance on whole body exercise tasks and the onset of such fatigue prompts a series of cardiorespiratory reflexes (Dempsey et al, 2014). This process is triggered by alterations in both systemic neural and chemical stimuli which modifies the global physiological responses seeking to sustain sufficient respiratory function and locomotor function. The key mechanisms here are concerned with important changes in both cardiorespiratory and perceptual responses, identified as important factors in the early termination of exercise tasks.